Genome-Wide Transposon Mutagenesis of Borrelia burgdorferi for Identification of Phenotypic Mutants - Stewart, Philip E. (American Society for Microbiology, 2004)
The spirochete Borrelia burgdorferi is the causative agent of Lyme disease, the leading vector-borne illness in the United States. Many of the genetic factors affecting spirochete morphology and physiology are unknown due to the limited genetic tools available and the large number of open reading frames with unknown functions. By adapting a mariner transposon to function in B. burgdorferi, we have developed a random mutagenesis system that tags the mutated locus for rapid identification. Transposition occurs at saturating levels in B. burgdorferi and appears to be random, targeting both linear and circular replicons. By combining the transposon system with a screen for factors affecting growth rate, mutations were readily identified in genes putatively involved in cell division and chemotaxis and a hypothetical open reading frame involved in outer membrane integrity. The successful adaptation of a mariner transposon to function in B. burgdorferi should aid in identifying virulence factors and novel gene products related to spirochete physiology.